Back Cover: Plasma Process. Polym. 1∕2015. Issue 1 (January 2015) - Huang, Xunzhi; Li, Yongsheng; Zhong, Xiaoxia; Rider, Amanda E.; Ostrikov, Kostya (Ken)
<x xml:space="preserve">Abstract</x> Back Cover: Carbon quantum dots were synthesized by using plasma‐assisted liquid phase nanofabrication at ambient conditions. The produced C‐dots with a predominant graphitic structure are of relatively uniform size and blue luminescence with the emission peak of C‐dots shifting from 443 nm to more than 456 nm as the excitation sources being varied from 360 to 410 nm. Further details can be found in the article by Xiaoxia Zhong et. al. on page 59. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>